REVOLUTIONIZING NEW DRUG RESEARCH: THE ROLE OF AI AND MACHINE LEARNING IN THE DISCOVERY OF NEW ANTIBIOTICS - Chrobak , Daria (Collection of scientific papers «ΛΌГOΣ», 2023)
Recent technological advances have revolutionized drug discovery. Artificial intelligence (AI) and machine learning (ML) are among the most important new tools being used to identify novel drug targets. This study examines the role of AI and ML in the discovery of new antibiotics, such as abaucin, a process that involves the identification and study of small molecules that could be used as drugs to treat a variety of diseases. It discusses how AI and ML are used to analyze large datasets, identify previously unknown abaucin targets, and study the molecular interactions of known abaucins. It also examines the challenges associated with using AI and ML for drug discovery, such as the need for large datasets and complexity of molecular interactions. Finally, this paper provides an outlook on the potential of AI and ML to revolutionize drug research in the future.